The Effectiveness of Satintelkam Raising Activities in Handling Conflict Between the Pasuruan Community and PT. Fresh Natural Partner at Pasuruan Police - Wiratama, Muhammad Susfi (Indonesian Journal of Police Studies, 2024)
PT. Mitra Alam Segar is one of the packaged beverage industries in Pasuruan Regency. The impact of the company was felt by residents of Mojoparon Village who complained about river pollution and dry well water. This caused residents to stage demonstrations and disrupt public security and order. Therefore, effective conflict management is needed to maintain social security and order to remain conducive. This research uses a descriptive qualitative approach with field research methods. This research uses Management Theory accompanied by Management Concepts, Cooperation Concepts, Effectiveness Concepts, Intelligence Activity Concepts, Mobilization Concepts, Conflict Handling Concepts, Community Concepts, and Company Concepts. The results of the research show that the efforts of the Pasuruan Police Satintelkam to gather intelligence as a mediator in the conflict between PT. Mitra Alam Segar and the residents of Mojoparon have not operated effectively. This is due to the competence of human resources who still do not follow the Dikjur and Dikbang, targets who have a personal interest in the conflict, and a lack of community support. Based on the results of the research above, the author recommends making efforts to increase human resource competency with Dikjur and Dikbang, establishing and fostering an intelligence network with NGOs, and establishing and fostering an intelligence network with community leaders and village officials.